2022
DOI: 10.1186/s12913-022-08280-z
|View full text |Cite
|
Sign up to set email alerts
|

Expanding access to substance use services and mental health care for people with HIV in Alabama, a technology readiness assessment using a mixed methods approach

Abstract: Background Alabama is one of seven priority states for the National Ending the HIV Epidemic Initiative due to a large rural burden of disease. Mental health (MH) and substance use disorders (SUD) represent obstacles to HIV care in rural areas lacking Medicaid expansion and infrastructure. Evidence-informed technologies, such as telehealth, may enhance SUD and MH services but remain understudied in rural regions. Methods We conducted a readiness ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In 2019, there were 4065 persons living with HIV receiving care at one of the participating +STEP sites. Initial findings from aim 1 of this study are available at BMC Health Services Research [42]. Using data from patient surveys and key staff members' qualitative interviews, this study found that all participating RWHAP-funded clinics were ready and willing to implement and integrate ePRO screening for MH and SUD followed by telehealth services as part of their treatment strategy.…”
Section: Resultsmentioning
confidence: 93%
“…In 2019, there were 4065 persons living with HIV receiving care at one of the participating +STEP sites. Initial findings from aim 1 of this study are available at BMC Health Services Research [42]. Using data from patient surveys and key staff members' qualitative interviews, this study found that all participating RWHAP-funded clinics were ready and willing to implement and integrate ePRO screening for MH and SUD followed by telehealth services as part of their treatment strategy.…”
Section: Resultsmentioning
confidence: 93%
“…Initial findings from aim 1 of this study are available at BMC Health Services Research [ 42 ]. Using data from patient surveys and key staff members’ qualitative interviews, this study found that all participating RWHAP-funded clinics were ready and willing to implement and integrate ePRO screening for MH and SUD followed by telehealth services as part of their treatment strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Interviews with key staff explored technological capacity and organizational readiness for change using the CFIR. Additional methodological details for aim 1 have been published in BMC Health Services Research [ 39 ]. The Implementation data will be abstracted from scheduling logs, training logs, and the electronic medical record (EMR) at each clinic site every 2 months to characterize the clinic and patient adoption and penetration of +STEP.…”
Section: Methodsmentioning
confidence: 99%
“…Although effective treatment is available for both these chronic conditions, access to these treatments can be a challenge, which has led to significant gaps in treatment [68]. Difficulties in access to treatment can stem from physical distances from a treatment site, difficulties with arranging for time away from home or work to attend clinical appointments, prohibitive treatment costs, and the paucity of specialist care [9,10]. Remarkably, 27% of the counties in the US are characterized by the complete absence of psychiatrists [11].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, 27% of the counties in the US are characterized by the complete absence of psychiatrists [11]. Rural residents are noteworthy for having limited access to in person psychiatric care [9,11]. Even more troubling, it appears that issues of access occur independently of the patients’ health insurance status.…”
Section: Introductionmentioning
confidence: 99%